A Xanthium-like structured lithium-sulfur battery positive electrode material and its preparation method and application

By adopting ZnSe-VO2@rGO/S composite material with a xanthium-shaped structure as the positive electrode material of lithium-sulfur battery, the shuttle effect, volume expansion and conductivity of lithium-sulfur battery are solved, and its cycle stability and rate performance are significantly improved.

CN115241421BActive Publication Date: 2025-04-11NANTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210687047.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-16
Publication Date
2025-04-11
Estimated Expiration
2042-06-16

AI Technical Summary

Technical Problem

Lithium-sulfur batteries have problems such as shuttle effect, severe volume expansion, poor conductivity, cycle stability and safety performance.

Method used

The ZnSe-VO2@rGO/S composite material with a xanthium-shaped structure is used as the cathode material of lithium sulfur batteries. Graphene oxide and xanthium-shaped vanadium dioxide are reduced through zinc selenide quantum dot modification to increase the conductivity and active sites of the material, and the contact area with sulfur is increased through the xanthium-shaped structure to inhibit the shuttle effect.

Benefits of technology

It improves the cycle stability and rate performance of lithium-sulfur batteries, suppresses the shuttle effect, improves the electrochemical performance, and alleviates the volume expansion problem.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115241421B_ABST
    Figure CN115241421B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of preparation of positive electrode materials for lithium-sulfur batteries, and discloses a positive electrode material for lithium-sulfur batteries with a Xanthium-like structure, and a preparation method and application thereof, wherein the preparation method comprises: dissolving ammonium metavanadate and dihydrated oxalic acid in a GO solution, and then performing a hydrothermal reaction to prepare Xanthium-like VO2@rGO; then adding a ZnSe QDs suspension to prepare ZnSe‑VO2@rGO; and finally preparing ZnSe‑VO2@rGO / S with sulfur powder by a melting method. The positive electrode material of the present invention is applied to lithium-sulfur batteries, which can improve the cycle stability and rate performance of lithium-sulfur batteries, and at the same time suppress the shuttle effect problem in lithium-sulfur batteries, thereby improving the electrochemical performance of lithium-sulfur batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium-sulfur battery positive electrode material preparation, and specifically relates to a lithium-sulfur battery positive electrode material with a Xanthium-like structure, and a preparation method and application thereof. Background Art

[0002] Lithium-sulfur batteries (LSBs) have a high energy density (2600 Wh kg -1 ), high theoretical specific capacity (1675 mAh g -1 ), low cost, excellent environmental friendliness and other advantages, but its application is hindered by some key problems. 1) Both elemental sulfur and lithium sulfide produced by discharge are insulators. As electrode materials, their active material utilization rate is low and their conductivity is poor; (2) During the charge and discharge process, the conversion of elemental sulfur and lithium sulfide will cause the volume of the positive electrode to change, causing the battery capacity to decay and even destroy the battery structure; (3) The shuttle effect of polysulfide. When lithium polysulfide is dissolved in an organic electrolyte, a concentration difference is generated between the positive and negative electrodes of the battery, causing lithium polysulfide to shuttle between the positive and negative electrodes. Due to the shuttle effect, electronically insulating low-sulfide lithium (Li2S / Li2S2) is deposited on the surface of the negative lithium, reducing the ion conductivity and losing a large amount of active material (sulfur), thereby causing the battery capacity to decrease and the life to be shortened. Therefore, the shuttle effect, severe volume expansion, poor conductivity, cycle stability and safety performance of lithium-sulfur batteries in the prior art have become technical problems that need to be solved urgently by technicians in this field. Summary of the invention

[0003] Technical issues solved:

[0004] The present application aims at the deficiencies of the prior art and solves the technical problems of the prior art such as the shuttle effect, severe volume expansion, poor conductivity, cycle stability and safety performance of lithium-sulfur batteries, and provides a lithium-sulfur battery positive electrode material with a cocklebur-like structure and a preparation method and application thereof. The lithium-sulfur battery positive electrode material can improve the cycle stability and rate performance of the lithium-sulfur battery, while suppressing the shuttle effect problem in the lithium-sulfur battery and improving the electrochemical performance of the lithium-sulfur battery.

[0005] Technical solution:

[0006] To achieve the above objectives, this application is implemented through the following technical solutions:

[0007] A lithium-sulfur battery positive electrode material with a cocklebur-like structure, the lithium-sulfur battery positive electrode material is a ZnSe-VO2@rGO / S composite material, the lithium-sulfur battery positive electrode material comprises zinc selenide quantum dots modified reduced graphene oxide / xanthium-like vanadium dioxide and the structure is used as the main body to load sulfur, the particle size of the zinc selenide quantum dots is 4-6 nm; the reduced graphene oxide is a layered nanostructure, allowing fast electron / ion transfer; the vanadium dioxide is a cocklebur-like structure, and the nanorods on the surface of VO2 better capture polysulfides by increasing the contact area.

[0008] A method for preparing a positive electrode material for a lithium-sulfur battery with a Xanthium-like structure, comprising the following steps:

[0009] Step 1: Dissolve zinc nitrate hexahydrate in deionized water under magnetic stirring, add 3-mercaptopropionic acid (MPA), adjust the pH to 11.0-11.2, inject sodium hydride selenide solution under inert gas protection, and heat reflux reaction to obtain zinc selenide quantum dot solution (ZnSe QDs);

[0010] Step 2: Under magnetic stirring, ammonium metavanadate and oxalic acid dihydrate were dissolved in the GO solution and stirred vigorously for 30 minutes. Next, the mixture was transferred to a Teflon-lined container and heated in a drying oven. Then, the blue-black precipitate was washed with ethanol and deionized water and vacuum dried to obtain the VO2@rGO composite material.

[0011] Step 3: Disperse the obtained VO2@rGO into the ZnSe quantum dot suspension solution, and stir vigorously for 20 minutes under the condition of passing N2; wash with deionized water and isopropanol, centrifuge, and then vacuum dry to obtain the ZnSe-VO2@rGO composite material;

[0012] Step 4: The ZnSe-VO2@rGO composite material and sulfur powder are mixed and ground for 20 to 30 minutes, and then reacted under the protection of inert gas. Finally, the reactor is placed in a 155° C. forced air drying oven for 12 hours to obtain ZnSe-VO2@rGO / S.

[0013] Furthermore, in the second step, the usage ratio of the ammonium metavanadate, oxalic acid dihydrate and graphene oxide is (0.52~1.05) g: (1.02~2.04) g: (30~40) ml (1 mg / ml), the heating time is 18-24 hours, and the temperature is 180°C.

[0014] Furthermore, in the third step, the dosage ratio of VO2@rGO and zinc selenide quantum dot solution is (0.2~0.4) g: (100~150) ml.

[0015] Furthermore, in the fourth step, the mass ratio of zinc selenide quantum dot modified reduced graphene oxide / Xanthium sibiricum-like vanadium dioxide to sulfur powder is (6-7):(4-3).

[0016] The present application also discloses the application of a Xanthium-like structured lithium-sulfur battery positive electrode material in a lithium-sulfur battery.

[0017] Furthermore, the preparation method of the sodium selenide solution in the first step is: under ice bath conditions, selenium powder and sodium borohydride are dissolved in deionized water, and react for 6 to 8 hours to obtain a sodium selenide solution; the molar ratio of sodium borohydride to selenium powder is 2:1.

[0018] Furthermore, in the first step, the molar ratio of sodium hydroselenide to zinc nitrate hexahydrate is 1:5.

[0019] Furthermore, in the first step, the dosage ratio of zinc nitrate hexahydrate, deionized water, and 3-mercaptopropionic acid is (1.19-2.97) g:400 ml:700 μL.

[0020] Furthermore, the temperature of the heating reflux reaction in the first step is 80-100° C., and the time is 80-120 minutes.

[0021] The working principle of the above-mentioned Xanthium-like lithium-sulfur battery positive electrode material and its preparation method and application is that polar vanadium dioxide and zinc selenide can adsorb polysulfides to inhibit the shuttle effect, while the Xanthium-like vanadium dioxide can increase the contact area with sulfur and reduce the loss of active sulfur. Reducing graphene oxide can increase the conductivity of the material and alleviate volume expansion to a certain extent.

[0022] Beneficial effects:

[0023] The present application provides a Xanthium-like structured lithium-sulfur battery positive electrode material and a preparation method and application thereof, which have the following beneficial effects compared with the prior art:

[0024] 1. In the positive electrode material of the present application, reduced graphene oxide is used as a conductive framework to provide fast electron / ion transmission channels. The zinc selenide quantum dots modified on the surface of reduced graphene oxide and vanadium dioxide are polar materials with small particle size and good dispersibility. Modification on the surface of reduced graphene oxide and vanadium dioxide can provide more active sites. On the one hand, the zinc selenide quantum dots are evenly distributed on the surface, ensuring direct contact between sulfur and ZnSe-VO2@rGO composite materials, which is beneficial to improving the conductivity and stability of the positive electrode material. On the other hand, the zinc selenide quantum dots can effectively chemically adsorb polysulfides, which can significantly inhibit the shuttling effect of polysulfides between the positive and negative electrodes.

[0025] 2. In the cathode material of the present application, on the one hand, the porous network structure of reduced graphene oxide can accommodate the volume expansion caused by the conversion of sulfur into lithium sulfide, and on the other hand, the pores between vanadium dioxide can also alleviate the volume expansion and ensure the integrity of the cathode material structure.

[0026] 3. In the cathode material of the present application, the porous structure of VO2 allows ions to diffuse rapidly through the formed tunnels. Under the induction of graphene oxide, thorny VO2 nanorods grow on the carambola-like VO2 nanostructure to form a cocklebur-like structure. At the same time, the thorny VO2 nanorods better capture polysulfides by increasing the contact area.

[0027] 4. Yuan et al. designed a CoSe2 / CS cathode composite material. After 200 cycles at 0.5 C, the discharge capacity of the CoSe2 / CS composite cathode was 550.6 mAh g -1 When cycled at current densities of 0.1, 0.2, 0.5, 1, and 2 C, the specific capacities of the CoSe2 / CS composite cathode were 1147.7, 830.8, 640.3, 540, and 457.6 mAh g, respectively. -1 Yuan et al. designed a flower-like FeS / CS cathode composite material, which had a capacity retention rate of only 66.2% after 100 cycles at 0.1 C. The specific capacity of FeS / CS at 2 C was 360 mAh g -1 When the current density returned to 0.1 C, the specific capacity recovered to 725 mAh g -1 .

[0028] 5. The initial specific capacity of the positive electrode material used in the lithium-sulfur battery at 0.2 C is as high as 1026.1 mAh g -1 , reaching 712.3 mAh g at 2 C -1 It also has good cycle performance, with a capacity retention rate of 89.1% after 150 cycles at 0.5 C. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a scanning electron microscope (SEM) image of vanadium dioxide obtained in the preparation process of Example 1 of the present application;

[0030] Figure 2 This is a scanning electron microscope (SEM) image of VO2@rGO obtained in Example 1 of the present application;

[0031] Figure 3 This is a transmission electron microscope (TEM) image of ZnSe-VO2@rGO obtained in Example 1 of the present application;

[0032] Figure 4 This is a high-resolution transmission electron microscopy (HRTEM) image of ZnSe-VO2@rGO obtained in Example 1 of the present application;

[0033] Figure 5 The specific capacity and cycle performance diagram of the lithium-sulfur batteries of Example 1 and Comparative Examples 1 and 2 provided in this application at 0.5 C within 150 cycles;

[0034] Figure 6 The specific capacity and rate performance diagram of the lithium-sulfur batteries of Example 1 and Comparative Examples 1 and 2 provided in this application. DETAILED DESCRIPTION

[0035] In order to facilitate the understanding of the present invention, the principles and features of the present invention are comprehensively and carefully described below in conjunction with the accompanying drawings and preferred embodiments. The embodiments are only used to explain the present invention and are not intended to limit the scope of the present invention.

[0036] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0037] In order to further illustrate the present invention, the preparation method and application of the positive electrode material of a lithium-sulfur battery with a Xanthium-like structure provided by the present invention are described in detail below in conjunction with the embodiments.

[0038] Embodiment 1:

[0039] A method for preparing a positive electrode material for a lithium-sulfur battery with a Xanthium-like structure, comprising the following steps:

[0040] Step 1: Add 10 mL of deionized water to a mixture of 0.31 g of sodium borohydride and 0.32 g of selenium powder. The reaction is cooled in an ice bath at 0 °C for 6 hours. The colorless supernatant is the sodium hydrogen selenide solution (NaHSe). During the reaction, the reaction vessel is covered with a rubber stopper with a needle to release the pressure of the generated hydrogen.

[0041] Step 2: Under magnetic stirring, 1.19 g zinc nitrate hexahydrate was dissolved in 400 ml deionized water, 700 μL 3-mercaptopropionic acid (MPA) was added, and 10 M sodium hydroxide solution was added to adjust the pH of the mixed solution to 11.0. Under nitrogen atmosphere protection, 1.2 ml of the NaHSe solution obtained in the first step was injected into the solution with a syringe and stirred for 30 minutes. Then, the mixed solution was transferred to a three-necked flask and refluxed at 80 °C for 80 minutes to obtain a zinc selenide quantum dot solution (ZnSeQDs);

[0042] Step 3: Under magnetic stirring, 0.52 g ammonium metavanadate and 1.02 g oxalic acid dihydrate were dissolved in 30 ml 1 mg / ml GO solution and stirred vigorously for 30 min. Next, the mixture was transferred to a 50 ml Teflon-lined container and heated in a drying oven at 180 °C for 18 h. Then, the blue-black precipitate was washed three times with ethanol and deionized water and vacuum dried at 60 °C for 12 h to obtain the VO2@rGO composite material.

[0043] Step 4: Disperse 0.3 g of VO2@rGO obtained in step 3 into 100 ml of ZnSe quantum dot suspension solution, and stir vigorously for 20 minutes under the condition of passing N2; wash with deionized water and isopropanol, centrifuge, and then vacuum dry to obtain ZnSe-VO2@rGO composite material;

[0044] Step 5: Mix 0.35 g of the ZnSe-VO2@rGO composite material described in the fourth step and 0.15 g of sulfur powder and grind them for 20 minutes. Then, put the ground powder into a reactor under an argon atmosphere in a glove box. Finally, place the reactor in a 155°C forced air drying oven to react for 12 hours to obtain ZnSe-VO2@rGO / S.

[0045] Figure 1 is a scanning electron microscope (SEM) image of vanadium dioxide obtained during the preparation process of this embodiment. Figure 1 It can be seen that VO2 is shaped like a star fruit, and each VO2 has six arms. From the illustration, it can be seen that the star fruit-like structure is self-assembled by six VO2 nanosheets. Figure 2 This is a scanning electron microscope (SEM) image of VO2@rGO. Figure 2 It can be seen that rGO sheets are embedded or wrapped in the star fruit clusters composed of VO2, indicating that the star fruit-like VO2 aggregates together and assembles with rGO sheets during the hydrothermal growth process, and that many nanorods grow on the surface of the star fruit-like VO2 under the induction of GO during the hydrothermal reaction, changing its structure into that of Xanthium sibiricum, and at the same time GO is reduced to rGO. Figure 3 This is the transmission electron microscope (TEM) image of ZnSe-VO2@rGO. A large number of VO2 nanorods stand upright on the surface of the carambola-shaped VO2 and are wrapped by rGO sheets on the outside. Figure 4 This is a high-resolution transmission electron microscopy (HRTEM) image of ZnSe-VO2@rGO obtained in this example. It can be seen in the image that many ZnSe quantum dots are modified on the surface of reduced graphene oxide. The size of these ZnSe quantum dots is about 3~6 nm, and the lattice spacing of the two substances is clearly visible.

[0046] Step 6: Preparation of slurry: 0.40 g of ZnSe-VO2@rGO / S, 0.12 g of conductive carbon black and 0.06 g of binder LA133 were mixed, ground and mixed in an agate mortar to make a slurry, and the slurry was evenly coated on aluminum foil by a doctor blade method, and dried at 60 °C for 12 h to obtain a positive electrode sheet;

[0047] Step 7: Making electrode sheets: Cut the positive electrode sheets into circular electrode sheets with a diameter of 16 mm;

[0048] Step 8. Preparation of lithium-sulfur battery: Use the prepared circular electrode as the positive electrode, Celgard 2500 as the separator, and the commercial metal lithium sheet as the negative electrode. Add 0.1M LiNO3+1M LiTFSI DOL / DME (volume ratio 1:1) electrolyte and assemble the 2032 button battery in an argon-filled glove box with a water and oxygen content of less than 0.1 ppm. After standing for 12 hours, test the electrochemical performance.

[0049] Embodiment 2:

[0050] A method for preparing a positive electrode material for a lithium-sulfur battery with a Xanthium-like structure, comprising the following steps:

[0051] Step 1: Add 20 mL of deionized water to a mixture of 0.62 g of sodium borohydride and 0.64 g of selenium powder. The reaction is cooled in an ice bath at 0 °C for 8 hours. The colorless supernatant is sodium hydride selenide solution (NaHSe). During the reaction, the reaction vessel is covered with a rubber stopper with a needle to release the pressure of the generated hydrogen.

[0052] Step 2: Under magnetic stirring, 1.5 g zinc nitrate hexahydrate was dissolved in 400 ml deionized water, 700 μL 3-mercaptopropionic acid (MPA) was added, and 5 M sodium hydroxide solution was added to adjust the pH of the mixed solution to 11.2. Under the protection of nitrogen atmosphere, 1.4 ml of the NaHSe solution obtained in the first step was injected into the solution with a syringe and stirred for 30 minutes. Then, the above mixture solution was transferred to a three-necked flask and refluxed at 100 °C for 120 minutes to obtain a zinc selenide quantum dot solution (ZnSeQDs);

[0053] Step 3: Under magnetic stirring, 1.05 g ammonium metavanadate and 2.04 g oxalic acid dihydrate were dissolved in 40 ml 1 mg / ml GO solution and stirred vigorously for 30 min. Next, the mixture was transferred to a 50 ml Teflon-lined container and heated in a drying oven at 180 °C for 20 h. Then, the blue-black precipitate was washed three times with ethanol and deionized water and vacuum dried at 60 °C for 12 h to obtain the VO2@rGO composite material.

[0054] Step 4: Disperse 0.4 g of VO2@rGO obtained in step 3 into 150 ml of ZnSe quantum dot suspension solution, and stir vigorously for 20 minutes under the condition of passing N2; wash with deionized water and isopropanol, centrifuge, and then vacuum dry to obtain ZnSe-VO2@rGO composite material;

[0055] Step 5: Mix 0.49 g of the ZnSe-VO2@rGO composite material described in the fourth step and 0.21 g of sulfur powder and grind them for 20 minutes. Then, put the ground powder into a reactor under an argon atmosphere in a glove box. Finally, place the reactor in a 155°C forced air drying oven to react for 12 hours to obtain ZnSe-VO2@rGO / S.

[0056] Comparative Example 1

[0057] (i) Preparation of vanadium dioxide (VO2): 0.52 g ammonium metavanadate and 1.02 g oxalic acid dihydrate were dissolved in 30 ml deionized water under magnetic stirring and stirred vigorously for 30 minutes. Next, the mixture was transferred to a 50 ml Teflon-lined container and heated in a drying oven at 180 °C for 18 hours. Then, the blue-black precipitate was washed three times with ethanol and deionized water and vacuum dried at 60 °C for 12 hours to obtain VO2.

[0058] (ii) Preparation of vanadium dioxide / sulfur composite material (VO2 / S): 0.35 g of vanadium dioxide (VO2) and 0.15 g of sublimated sulfur were ground in an agate mortar for 30 min. The ground powder was then placed in a reactor under an inert gas atmosphere in a glove box. The reactor was then placed in a 155°C forced air drying oven for reaction for 12 h.

[0059] (III) Preparation of slurry: 0.45 g of VO2 / S, 0.13 g of conductive carbon black and 0.065 g of binder LA133 were mixed, ground and mixed in an agate mortar to form a slurry, and the slurry was evenly coated on an aluminum foil by a doctor blade method, and dried at 60 °C for 12 h to obtain a positive electrode sheet.

[0060] (iv) Preparation of electrode sheets: Cut the dried positive electrode sheets into circular electrode sheets with a diameter of 16 mm.

[0061] (V) Preparation of lithium-sulfur battery: The prepared circular electrode was used as the positive electrode, Celgard 2500 as the separator, and the commercial metal lithium sheet as the negative electrode. An electrolyte of 0.1M LiNO3+1M LiTFSI in DOL / DME (volume ratio 1:1) was added and the 2032 type button battery was assembled in an argon-filled glove box with a water and oxygen content of less than 0.1 ppm. The electrochemical performance was tested after standing for 12 hours.

[0062] Comparative Example 2

[0063] (i) Preparation of VO2@rGO composite material: 0.52 g ammonium metavanadate and 1.02 g oxalic acid dihydrate were dissolved in 30 ml 1 mg / ml GO solution under magnetic stirring and stirred vigorously for 30 min. Next, the mixture was transferred to a 50 ml Teflon-lined container and heated in a drying oven at 180 °C for 18 h. Then, the blue-black precipitate was washed three times with ethanol and deionized water and vacuum dried at 60 °C for 12 h to obtain the VO2@rGO composite material.

[0064] (ii) Preparation of vanadium dioxide@reduced graphene oxide / sulfur composite material (VO2@rGO / S): 0.35 g VO2@rGO and 0.15 g sulfur powder in step (i) were mixed and ground for 20 minutes. The ground powder was then placed in a reactor under an argon atmosphere in a glove box. The reactor was then placed in a forced air drying oven at 155°C for 12 hours to obtain a VO2@rGO / S composite material.

[0065] (III) Preparation of slurry: 0.45 g of VO2@rGO / S, 0.13 g of conductive carbon black and 0.065 g of binder LA133 were mixed, ground and mixed in an agate mortar to form a slurry, and the slurry was evenly coated on an aluminum foil by a doctor blade method, and dried at 60 °C for 12 h to obtain a positive electrode sheet.

[0066] (iv) Preparation of electrode sheets: Cut the dried positive electrode sheets into circular electrode sheets with a diameter of 16 mm.

[0067] (V) Preparation of lithium-sulfur battery: The prepared circular electrode was used as the positive electrode, Celgard 2500 as the separator, and the commercial metal lithium sheet as the negative electrode. An electrolyte of 0.1M LiNO3+1M LiTFSI in DOL / DME (volume ratio 1:1) was added and the 2032 type button battery was assembled in an argon-filled glove box with a water and oxygen content of less than 0.1 ppm. The electrochemical performance was tested after standing for 12 hours.

[0068] Test Case

[0069] The lithium-sulfur batteries obtained in Example 1 and Comparative Examples 1 and 2 were subjected to constant current charge and discharge, cycle performance test and rate performance test using a charge and discharge instrument from Shenzhen Xinwei Co., Ltd. The test temperature herein was the ambient temperature of 26°C, and the charge and discharge voltage cutoff range was 1.6 to 3.0 V.

[0070] The specific capacity and cycle performance diagram of the lithium-sulfur battery in Example 1 and Comparative Examples 1 and 2 provided by the present invention within 150 cycles at 0.5 C. The discharge specific capacity of the lithium-sulfur battery assembled with ZnSe-VO2@rGO / S provided in Example 1 as the positive electrode material increases from 920.4 mAh g in the first cycle to 150 mAh g in the second cycle. -1 The discharge capacity after 150 cycles is 820.1 mAh g -1 , the capacity retention rate is 89.1%, the coulombic efficiency is about 99%, and it has very good cycle stability, while the specific capacity of comparative examples 1 and 2 is significantly lower than that of the lithium-sulfur battery with ZnSe-VO2@rGO / S as the positive electrode. The specific capacity and rate performance diagram of the lithium-sulfur battery of Example 1 and Comparative Examples 1 and 2 provided by the present invention. The rate performance of the lithium-sulfur battery assembled with ZnSe-VO2@rGO / S as the positive electrode material provided in Example 1 at 0.2 C to 2C, the discharge specific capacity at 0.2 C, 0.5 C, 1 C, and 2 C are 1041.3, 901.7, 802.6, and 712.3 mAh g -1 When the current density rises back to 2 C, the corresponding capacity recovers to 850.6 mAh g -1 . However, the capacity of the lithium-sulfur battery with the materials in comparative examples 1 and 2 as electrodes decays rapidly, the discharge specific capacity and stability are relatively poor, the shuttle effect is serious, and the utilization rate of active materials is extremely low. The lithium-sulfur battery with ZnSe-VO2@rGO / S material as electrode has excellent rate performance and high stability, showing excellent electrochemical performance, and has good initial specific capacity, cycle performance and rate performance.

[0071] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A method for preparing a positive electrode material for a lithium-sulfur battery with a Xanthium-like structure, characterized in that: The positive electrode material of the lithium-sulfur battery is a ZnSe-VO2@rGO / S composite material, which includes zinc selenide quantum dots modified reduced graphene oxide / xanthium-like vanadium dioxide and uses the structure as the main body to load sulfur, and the particle size of the zinc selenide quantum dots is 4-6 nm; the reduced graphene oxide is a layered nanostructure, allowing rapid electron / ion transfer; the vanadium dioxide is a xanthium-like structure, and the nanorods on the surface of VO2 better capture polysulfides by increasing the contact area. The preparation method of the positive electrode material of the lithium-sulfur battery with a xanthium-like structure includes the following steps: Step 1: Dissolve zinc nitrate hexahydrate in deionized water under magnetic stirring, add 3-mercaptopropionic acid MPA, adjust the pH to 11.0-11.2, inject sodium hydride selenide solution under inert gas protection, and heat reflux reaction to obtain zinc selenide quantum dot solution ZnSe QDs; Step 2: Under magnetic stirring, ammonium metavanadate and oxalic acid dihydrate were dissolved in the GO solution and stirred vigorously for 30 minutes. Next, the mixture was transferred to a Teflon-lined container and heated in a drying oven. Then, the blue-black precipitate was washed with ethanol and deionized water and vacuum dried to obtain the VO2@rGO composite material. Step 3: Disperse the obtained VO2@rGO into the ZnSe quantum dot suspension solution, and stir vigorously for 20 minutes under the condition of passing N2; wash with deionized water and isopropanol, centrifuge, and then vacuum dry to obtain the ZnSe-VO2@rGO composite material; Step 4: The ZnSe-VO2@rGO composite material and sulfur powder are mixed and ground for 20 to 30 minutes, and then reacted under the protection of inert gas. Finally, the reactor is placed in a 155° C. forced air drying oven for 12 hours to obtain ZnSe-VO2@rGO / S.

2. The method for preparing the positive electrode material of a lithium-sulfur battery with a Xanthium-like structure according to claim 1, characterized in that: In the second step, the dosage ratio of the ammonium metavanadate, oxalic acid dihydrate and GO is (0.52~1.05) g: (1.02~2.04) g: (30~40) ml-1 mg / ml, the heating time is 18-24 hours, and the temperature is 180°C.

3. The method for preparing the positive electrode material of a lithium-sulfur battery with a Xanthium-like structure according to claim 1, characterized in that: In the third step, the dosage ratio of VO2@rGO and zinc selenide quantum dot solution is (0.2~0.4) g: (100~150) ml.

4. The method for preparing the Xanthium-like lithium-sulfur battery positive electrode material according to claim 1, characterized in that: In the fourth step, the mass ratio of the ZnSe-VO2@rGO composite material to the sulfur powder is (6~7):(4~3).

5. The method for preparing the Xanthium-like lithium-sulfur battery positive electrode material according to claim 1, characterized in that: The preparation method of the sodium selenide solution in the first step is: dissolving selenium powder and sodium borohydride in deionized water under ice bath conditions, reacting for 6 to 8 hours to obtain a sodium selenide solution; the molar ratio of the sodium borohydride to the selenium powder is 2:

1.

6. The method for preparing the Xanthium-like lithium-sulfur battery positive electrode material according to claim 1, characterized in that: In the first step, the molar ratio of sodium hydride selenide to zinc nitrate hexahydrate is 1:

5.

7. The method for preparing the positive electrode material of a lithium-sulfur battery with a Xanthium-like structure according to claim 1, characterized in that: In the first step, the dosage ratio of zinc nitrate hexahydrate, deionized water, and 3-mercaptopropionic acid is (1.19-2.97) g:400 ml:700 μL.

8. The method for preparing the positive electrode material of a lithium-sulfur battery with a Xanthium-like structure according to claim 1, characterized in that: The temperature of the heating reflux reaction in the first step is 80-100° C. and the time is 80-120 minutes.

9. Use of the Xanthium-like lithium-sulfur battery positive electrode material prepared by the preparation method according to claim 1 in a lithium-sulfur battery.